Paysagéités de la représentation - Catherine Chomarat-Ruiz (Projets de Paysage)
The text published corresponds to the viva voce of the thesis for the habilitation of Catherine Chomarat-Ruiz, delivered on 11 January 2011, at the École Nationale Supérieure du Paysage de Versailles-Marseille. It was prepared under the direction of Jacques Leenhardt (supervisor at the École des hautes études en sciences sociales). She was granted this diploma by a jury made up of Augustin Berque (supervisor at the EHESS, Paris), Pierre Donadieu (professor at the École nationale supérieure du paysage of Versailles-Marseille), Michaël Jakob (professor at the Haute École du paysage, d’ingénierie et d’architecture, Geneva), Monique Mosser (research engineer at the CNRS, André Chastel Centre, Paris) and Claude Reichler (professor at the university of Lausanne). After having briefly reminded the audience of the content of the thesis submitted last June, this viva explains what is the situation of "landscapetics" – a unitary science of landscape introduced by herself – and of her scientific programme for the next six years.